2010
DOI: 10.1007/s10495-010-0560-2
|View full text |Cite
|
Sign up to set email alerts
|

The ribonucleotide reductase R1 subunits of herpes simplex virus types 1 and 2 protect cells against TNFα- and FasL-induced apoptosis by interacting with caspase-8

Abstract: We previously reported that HSV-2 R1, the R1 subunit (ICP10; UL39) of herpes simplex virus type-2 ribonucleotide reductase, protects cells against apoptosis induced by the death receptor (DR) ligands tumor necrosis factor-alpha-(TNFa) and Fas ligand (FasL) by interrupting DR-mediated signaling at, or upstream of, caspase-8 activation. Further investigation of the molecular mechanism underlying HSV-2 R1 protection showed that extracellularregulated kinase 1/2 (ERK1/2), phosphatidylinositol 3-kinase (PI3-K)/Akt,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 70 publications
2
76
0
Order By: Relevance
“…S6D), consistent with the previous observation that ICP6 is dispensable for virus multiplication in dividing cells (30). It has been demonstrated that ICP6 constitutively interacts with caspase-8 and RIP1 through its reductase domain and functions in an antiapoptotic role in death triggered by TNF-α, FasL, or TLR3 (31,32). Although the N-terminal RHIM sequence of ICP6 was shown to be dispensable for the interaction with RIP1 and caspase-8, we have found that it is essential for the interaction with RIP3 (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…S6D), consistent with the previous observation that ICP6 is dispensable for virus multiplication in dividing cells (30). It has been demonstrated that ICP6 constitutively interacts with caspase-8 and RIP1 through its reductase domain and functions in an antiapoptotic role in death triggered by TNF-α, FasL, or TLR3 (31,32). Although the N-terminal RHIM sequence of ICP6 was shown to be dispensable for the interaction with RIP1 and caspase-8, we have found that it is essential for the interaction with RIP3 (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In light of previous reports showing the key role of caspase 8 activation in poly(I ⅐ C)-induced apoptosis (29,72), the present study was undertaken to validate the hypothesis that HSV R1s could prevent poly(I ⅐ C)-induced apoptosis by virtue of their ability to inhibit caspase 8 activation (15). Our demonstration that HSV R1s impair the apoptotic host defense mechanism triggered by dsRNA adds a new facet to the ability of HSVs to manipulate antiviral responses.…”
Section: Individually Expressed Hsv R1s Counteracted Caspase 8 Activamentioning
confidence: 61%
“…HSVs encode different cell death suppressors, several of them conferring resistance to apoptosis elicited by the process of viral replication itself and/or by extrinsic stimuli linked to immune effector cell cytotoxicity or activation of death receptors (25). Among the viral genes involved in the control of apoptosis, UL39, which encodes the R1 subunit of HSV ribonucleotide reductase (HSV R1), protects epithelial cells from apoptosis induced by the death receptor ligands tumor necrosis factor alpha (TNF-␣) and Fas ligand (FasL) (15,44). Double-stranded RNA (dsRNA), one of the major viral products involved in the cellular sensing of viral invasion, triggers both IFN and apoptosis responses (17,29).…”
Section: Individually Expressed Hsv R1s Counteracted Caspase 8 Activamentioning
confidence: 99%
See 1 more Smart Citation
“…Herpes simplex virus 1 (HSV-1) and HSV-2 encode a number of proteins that inhibit apoptosis (9,10), including protein kinase US3 (11,12), glycoprotein J (gJ) (13), and latency-associated transcript (LAT) (14). In addition, HSV mutants deleted for ICP4, ICP27, UL39, and gD undergo apoptosis in a cell-type-specific manner (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%